Experimental and modeling on hydrate phase equilibrium conditions for hydrogen-containing gas mixtures in pure water and brines. (April 2023) - Li, Rui; Wang, Xiao-Hui; Cao, Bo-Jian; Chen, Hong-Nan; Pang, Wei-Xin; Li, Qing-Ping; Sun, Yi-Fei; Ma, Qing-Lan; Sun, Chang-Yu; Chen, Guang-Jin
Highlights: Hydrate phase equilibrium conditions for hydrogen-containing gas mixtures were measured. The feed gas are binary and ternary gas mixtures, while aqueous solutions are pure water and brine. WS and vdW mixing rules were applied in predicting hydrate phase equilibrium conditions. The AADP of PT-WS model is 4.61%, exhibiting a better performance for available data. Abstract: Hydrate-based technology is considered as one of potential ways for hydrogen separation and storage. Additionally, it has been reported that injecting CO2 /H2 mixture is an effective approach to the enhancement of natural gas hydrate exploitation. Hence the determination of hydrate formation conditions of hydrogen containing gas mixtures is of fundamental significance. A series of hydrate formation conditions of hydrogen-containing gas mixtures were then measured under 273.8 to 285.5 K and 2.61 to 10.52 MPa, including 3 binary (CH4 + H2 ) gas mixtures and 5 ternary (CH4 + CO2 + H2 ) gas mixtures in pure water, as well as 8 ternary (CH4 + CO2 + H2 ) gas mixtures in aqueous solutions of NaCl and Na2 SO4 . Meanwhile, a thermodynamic model for predicting hydrate formation conditions of hydrogen-containing systems were developed, in which Chen–Guo hydrate model was used to calculate the fugacities of guest species in hydrate phase and Patel–Teja equation of state was used to calculate the fugacities of guest components in gas phase and those of water in aqueous solutions. Two mixing rules, van der Waals mixing rule and Wang-Sandler mixing rule, were applied in parallel to determine the values of parameters of Patel–Teja equation of state. The overall average absolute deviation on formation pressure for 273 data points is 4.61 % when using Wang-Sandler mixing rule while it is 5.70 % when using van der Waals mixing rule. The experimental data and prediction method presented might be of significance for both exploitation of natural gas hydrate via injecting CO2 /H2 mixture as well as the purification of hydrogen via forming hydrate.